REKONSTRUKSI KEBIJAKAN PENGELOLAAN KAWASAN TENGGER BERBASIS NILAI-NILAI KOMUNAL EKOLOGIS - Purnawan Dwikora Negara (Legal Spirit, 2017)
The purpose of this study is to uncover and describe the policy of protecting the existence of Indigenous and Tribal Peoples and find the ideal development policy in Tengger region management reflected through Tengger’s Indigenous and Tribal Peoples. The findings show that: 1) the policy has provided protection for the existence of Indigenous and Tribal Peoples, including the Tenggerese people, as well as the philosophy of Pancasila, the 1945 Constitution, the MPR Decree, international arrangements, and national legislation. 2) In fact, although there are policies that ensure respect and protection, Indigenous Peoples are not fully protected, if this is reflected from the Tenggerese society, the main thing that keeps its existence unprotected is the conditional recognition in the constitution, sectoral laws and also the contribution to good conditional recognition, there is also a gap between the value of the policy and Tengger society in Tengger cultural space with different interests; 3) The alternative constructs that can be given to reduce the problem are: a) Carrying out the policy of the Principle of Recognition of Unconditional Meaning in the Constitution; b) Policy which is Based on Tengger Local Wisdom c) Policy prioritizing Principles of Participation d) Policies to strengthen community autonomy; e) Policy for the Establishment of National Commission on Indigenous and Tribal Peoples. Keywords: Policy Reconstruction, Tengger, Ecological Communal